Process modelling of friction stir welding of AA1100 aluminum alloy using a hexagon-shaped tool to optimize the process parameters - Indrawanto Indrawanto (BKS-TM Indonesia, 2025)
This paper presents process modeling of Friction Stir Welding (FSW) to optimize mechanical properties on the friction stir welded material of 1100 aluminum alloy. The model variables are tool rotational speed, translational feed rate, and axial force. The model is developed using a statistical engineering method known as Response Surface Methodology (RSM). The analysis of variance techniques has been used to illustrate the adequacy of the model. The effect of the welding parameters on mechanical properties, macro-structure, and micro-structure of friction stir welded joints have been analyzed in detail and the predicted trends are discussed. The developed mathematical model can be effectively used to predict the tensile strength of friction stir welded AA1100 aluminum alloy joints at the 95% confidence level.